Heritable Epichloë symbiosis shapes fungal but not bacterial communities of plant leaves - Nissinen, Riitta (Sci Rep, 2019)
Keystone microbial species have driven eco-evolutionary processes since the origin of life. However, due to our inability to detect the majority of microbiota, members of diverse microbial communities of fungi, bacteria and viruses have largely been ignored as keystone species in past literature. Here we tested whether heritable Epichloë species of pooidae grasses modulate microbiota of their shared host plant.